THE STUDY OF SACRED STONE SITES: FIELD RESEARCH EXPERIENCES (Philological Studies, 2019)
This paper aims to present the approaches to the study of sacred stones (in Republic of Macedonia) and to contribute toward discussions of different field research experiences. Particular emphasis is given to fieldwork techniques and research practice, as a primary resource of providing evidence and giving insight into explored cultures.
Keywords: fieldwork, research experiences, questionnaires, interviews, culture